Indigenous religious values: understanding work and rest - Masikane, Fikile Goodness (My University, 2017)
This thesis argues that indigenous (native, traditional) religious values and beliefs engender a more nuanced and alternative thought – as opposed to the existing capitalist definition or interpretation- of what emancipatory work is for black people; this alternative interpretation of emancipatory work, I suggest, is relevant to black people as it is defined by black people themselves and not those in power, this is in light of the broader South African black emancipation project. I have made use of the Shembe church’s concept of ‘rest’, as the theoretical framework, in order to answer the question: how if at all, does the Shembe church’s doctrine of the Sabbath rest [help us] conceptualize the problem of work for blacks in the post-apartheid South Africa? How, furthermore does this practice of the Sabbath rest [help us] conceptualize black liberation? Further, this study used the Shembe church’s doctrinal book (church manual or law book), which largely follows the laws or commandments presented in the book of Exodus (Bible). Adopting a qualitative research design, helped in using a method of biblical hermeneutics as a way to dissect and critically analyze the concepts of work and the proposed concept of rest as a way to begin to think of /and practice liberation through the lenses of Isaiah Shembe, the founding father of the movement. Isaiah Shembe understands the Sabbath rest in its literal sense of ‘inactivity’, this is done by taking the last day of the week off from work and any form of activity that an individual would partake in, in the week. Following this, rest for Isaiah Shembe provides a sense of practical and present/current freedom that individuals claim for themselves as opposed to freedom/liberation as something only hoped for in future, especially for the ever hopeful black people. It is through this understanding of ‘rest’ that, as Isaiah Shembe presents, helps us understand the problem of waged work, which has been ideally presented by the post-apartheid government, as an emancipatory tool to bridge the gap of inequality for black people. Given the reality of the growing gap of inequalities wagedwork, is evidently, never satisfactory as the individual is consistently working without reaping the necessary benefits. For Isaiah Shembe then, it becomes important to rethink and redefine the idea of what work is (for black people) which for him should be meant to elevate the individual mentally, intellectually, physically, and spiritually by allowing the individual to work creatively without imposition and supervision. At play, ultimately, Isaiah Shembe argues that by understanding rest, one will understand what work is and further how to work in order to get satisfaction. Key Words: work [waged], rest, emancipation, indigenous religious values
A research report submitted in fulfilment to the Degree of Master of Arts in Industrial Sociology in the Faculty of Humanities, University of the Witwatersrand, 2018
Keywords: Spirituality; Religion